Dormant No More: The Neurogical Impact of Herpes Simplex Virus Reactivation Following Traumatic Brain Injury - Johansyah, Theodorus Kevin Putra; Soetomo, Cindy Thiovany; Tiffany, Tiffany; Maliawan, Sri (Jurnal Neuroanestesi Indonesia, 2025)
Herpes simplex viruses (HSV), including HSV-1 and HSV-2, are neurotropic viruses capable of establishing lifelong latency in sensory ganglia and reactivating under various triggers, including traumatic brain injury (TBI). TBI induces secondary injury cascades such as neuroinflammation, excitotoxicity, and blood-brain barrier disruption, which create a conducive environment for HSV reactivation. The reactivation of HSV after TBI, particularly HSV-1 and HSV-2, can lead to significant neurological consequences, including encephalitis, cognitive decline, and the development of neurodegenerative diseases like Alzheimers disease and Chronic Traumatic Encephalopathy. Current therapeutic approaches focus on antiviral agents like acyclovir and valacyclovir, which manage acute HSV infection but are less effective in preventing long-term neurological damage. Emerging research highlights the potential of anti-inflammatory and neuroprotective strategies to complement antiviral therapies, aiming to reduce the neuronal damage caused by viral reactivation and inflammation. However, gaps remain in understanding the precise mechanisms linking TBI-induced neuroinflammation to HSV reactivation and its long-term impact on neurological health. This review synthesizes the current literature on the pathophysiology of HSV reactivation following TBI, and their contributions to acute and chronic neurological outcomes